2016
DOI: 10.32890/ijms.23.1.2016.10466
|View full text |Cite
|
Sign up to set email alerts
|

Work Stress, Pay Satisfaction, Psychological Empowerment and Organisational Commitment Among Academic Staff

Abstract: This study investigated the mediating effect of psychological empowerment on the relationship between work stress, pay satisfaction, and organisational commitment among academic staff in public universities. A total number of 297 academics responded to this study and Statistical Package Software for Social Science (SPSS) Version 21.0 was used to analyse the collected data. The results indicated that work stress is associated with organisational commitment, whereas pay satisfaction, psychological empowerment, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 35 publications
3
23
0
1
Order By: Relevance
“…In higher education institutions, stress involving academic staff primarily due to the responsibilities borne, which are not restricted to the process of teaching and learning but also fulfilling the demand as required in the Key Performance Indicators (KPI) of the universities (Darus, Azizan, & Ahmad, 2016). Nor Amalina, Huda, and Hejar (2016) reported that occupational stress is experienced by more than two-thirds of academic staff in every university.…”
Section: Literature Review Occupational Stress Stress Effect and Coping Strategiesmentioning
confidence: 99%
“…In higher education institutions, stress involving academic staff primarily due to the responsibilities borne, which are not restricted to the process of teaching and learning but also fulfilling the demand as required in the Key Performance Indicators (KPI) of the universities (Darus, Azizan, & Ahmad, 2016). Nor Amalina, Huda, and Hejar (2016) reported that occupational stress is experienced by more than two-thirds of academic staff in every university.…”
Section: Literature Review Occupational Stress Stress Effect and Coping Strategiesmentioning
confidence: 99%
“…According to Darus, Azizan, and Ahmad (2016), pay satisfaction is the fairly payment system which is significantly related to company commitment. The design of the pay system has four types of equity; internal equity, external equity, private equity and pay efficiency.…”
Section: A) Pay Level Satisfactionmentioning
confidence: 99%
“…Mental health and well-being are crucial aspects of an organization's performance and success (Page et al, 2009). According to current arguments, employees face new problems as the working circumstances of globalized economies, new regulations, and technology change (Darus et al, 2016;Jiang et al, 2017). These worldwide upheavals show that 25 percent of the world's workforce, including educators, is unhappy with their employment.…”
Section: Introductionmentioning
confidence: 99%